Implementasi Aplikasi EIGHT untuk Pengembangan Kompetensi Aparatur Sipil Negara - Dita Nurmadewi; Elin Cahyaningsih; Nanda Agrandis; Munif Ardiansyah; Budi Saputro (JSAI (Journal Scientific and Applied Informatics), 2025)
EIGHT (Academy for Government Human Capital Management Specialist) is a technology-based knowledge management system (KMS) designed to improve the management of the competency of the State Civil Apparatus (ASN). In an effort to support bureaucratic reform and improve public service quality, EIGHT integrates the Learning Management System (LMS) and Knowledge Management System (KMS), allowing ASN to access training materials, regulations, and important documents through an easily accessible digital platform. The Agile Software Development Life Cycle (SDLC) approach was chosen in the development of this system to ensure flexibility, rapid iteration, and responsiveness to user feedback. The research findings indicate that the EIGHT platform has successfully provided an efficient solution for managing ASN competencies, with easy access through the Single Sign-On (SSO) feature. Although some challenges remain in terms of integration and continuous updates, this system shows great potential in supporting the improvement of ASN professionalism and strengthening the culture of continuous learning within government organizations. This system is expected to become a model for the development of technology-based systems in the public sector in the future.